(3eWGdY GdCfhGQs - (3SQGL GdOjf eMehO Hf CHj HcQ GdGQehj,J (B682 (3g` s
(3ChdgG (B:s
(3hHYO agPG eNJUQ ai GdYdhe GdMbjbjI hGdeYGQa GdBdgjI SejJg HeWGdY GdCfhGQ hQJHJg Ydi WQajf GdChd ai GdefWb s
(3BNQgG (B:s
(3bO dG jchf GdMO GdJGe dG jbHd GdRjGOI hGdfbUGf eYfi hZjQg hbO GdbSe ai GdMSGH GdJUOjbGJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(240) s
Keywords: (3GdeLGejYs